Utilization of the Guard Post as a Business Place at Wisma Permai RT 06 - Lutters, Emmanuelle Litania; D.C., Vebyola Indah; Phoebe S.P., Bernadeth Chiquita; Harianto, Yohanes Kristianus; Efandaru, James; Setiawan, Valerio Sultan Agni; Utomo, Ariel Suryo; Setiadi, Widriyakara; Roosandriantini, Josephine; Hidayat, Anas (ABDIMAS ALTRUIS: Jurnal Pengabdian Kepada Masyarakat, 2024)
This community field study aimed to repair the damage to the business post on Rt 6 Wisma Permai Barat, which is an important source of income for local residents. The aim of this activity was to improve the functionality of the business post and increase the comfort of its occupants. The project involved initial site surveys, renovation planning, and post-renovation work. Seven community service program students from Darma Cendika University and several local residents collaborated on this project from March to July 2024 (5 months). The main activities carried out included painting, adding canopies and decorations, filling holes in walls, and leveling the expanded land with paving and plastering. Students and residents participated in the smooth running of this project. The result of this project is that the business post now looks cleaner and more attractive due to the new color scheme. The extension area becomes more comfortable, with additional shade and flatness. This community service project shows the significant impact of collaborative efforts between students and local communities in improving public infrastructure. This project was undertaken so that the upgraded business outpost would hopefully better fulfill its purpose and provide a more enjoyable environment for the business and its customers.